Rancang Bangun Sistem Monitoring Konsentrasi Kadar Garam pada Tambak Ikan Bandeng menggunakan Android - Nuzlya Ramadhana (Politeknik Negeri Malang, 2019)
In the cultivation of milkfish, water quality is very concerned about in order to minimize fish mortality when cultivated. Several important factors in the cultivation of milkfish are the level of salt content in the water, temperature and pH. Currently, farmers monitor water quality manually by coming directly to see water quality. If there are dead fish, the cultivator will replace the new water. This will have an impact on fish production which will decrease. The milkfish pond uses brackish water for pond waters. The salt content is between the sea water content and the fresh water content. The grade level may change from season to season. This change is due to biological processes that occur in these waters as well as the interaction between pond waters and the surrounding environment. The results showed that the results of the design of the salt concentration monitoring system in the milkfish ponds that have been carried out using Arduino Uno, conductivity sensors, pH sensors, temperature sensors, wifi modules, Mi-Fi and Smartphones to access android applications. The results of testing the microcontroller functionality that have been made are in accordance with the design and are running well. The system designed to transmit information in the form of salinity values, pH sensors, temperature sensors and TDS values ??with sensor accuracy that is linear with measurement results using conventional measuring instruments with the highest error values ??of 1.3%, 2.06%, 0.702% and 1.5 respectively. %.